Continuous Kolbe Electrolysis Using an Electrochemical Microreactor, Product Separation, and Electrolyte Recycling - Baumgarten, Nils; Etzold, Bastian J.M.; Löb, Patrick; Magomajew, Juri; Ziogas, Athanassios (Chemie Ingenieur Technik, 2024)
With our electrochemical microreactor and the use of an aqueous electrolyte it was possible to realize continuous Kolbe electrolysis including separation of the organic product phase, recycling of the aqueous electrolyte, and automated reconcentration of fatty acids based on inline Raman measurements. Electrolysis experiments revealed that the addition of aqueous KOH is essential to decrease the KHCO3 concentration and to stabilize the pH value of the electrolyte. Stable conversion (63–58 %) and Kolbe selectivity (90–92 %) could be achieved within 75 min. Removal of KHCO3 before reconcentration was provided as possible solution to maintain performance for increased electrolysis times.
Created from Fastlane, Scopus look-up
Keywords: Electrochemical microreactor; Electrolyte recycling; Fatty acids; Kolbe electrolysis; Radical dimerization